Takhrīj al-Ḥadīṡ Sebagai Metode Kritik Wacana: Menyingkap Bias Otoritas dalam Sejarah Transmisi Hadis - Nasution, Maslan; Aini, Putri Sagita Anugrah; Sajidah, Saffina; Siregar, Idris; Nasution , Syah Fitriani (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
This article departs from the epistemological problem in hadith studies, which positions takhrīj al-Ḥadīṡ primarily as a normative verification technique to determine the quality of narrations, thereby tending to overlook the dimensions of power relations, the production of authority, and the discursive dynamics at work in the history of hadith transmission. This approach limits the takhrīj’s ability to read the sanad selection process as a socio-intellectual practice laden with interests and scholarly hierarchies. This study aims to reconstruct takhrīj al-Ḥadīṡ as a tool of discourse criticism that enables the disclosure of authority bias in the formation of the hadith canon. The study uses a qualitative method based on literature studies with a critical discourse analysis approach to takhrīj texts, works of rijāl al-Ḥadīṡ, and the dominant sanad assessment practices in the classical tradition. The results of this study indicate that takhrīj operates as a non-neutral discursive practice, as it systematically reproduces certain authorities through hierarchies of narrators, privileging dominant transmission networks, and mechanisms of exclusion against narrations originating from marginalized or outside-the-mainstream figures. The analysis also reveals that the criteria for authenticity are not merely technical, but are articulated in the configuration of scholarly discourse that affirms the legitimacy of certain groups while limiting the possibility of alternative interpretations. The implications of this study emphasize the need to reposition takhrīj al-Ḥadīṡ in contemporary hadith studies as a critical-analytical tool capable of reading hadith not only as normative texts, but also as products of power relations and constructions of historical authority, thus opening up a more reflective and contextual reading space.